A Pd3L6 supramolecular cage incorporating photoactive [2.2]paracyclophane units. Issue 1 (8th November 2019) - Rota Martir, Diego; Delforce, Lucie; Cordes, David B.; Slawin, Alexandra M. Z.; Warriner, Stuart L.; Jacquemin, Denis; Zysman-Colman, Eli
Abstract : In this work we report two photoactive [2.2]paracyclophane (pCp) ligands and a luminescent Pd3 L6 cage incorporating these ligands, which exhibits blue emission both in solution and in the powder state. Abstract : [2.2]Paracyclophane (pCp) scaffolds, unlike many π-conjugated building blocks, have been rarely explored in supramolecular self-assembly. Herein we report the synthesis and characterization of two ligands, pCpd3py and pCpd4py, composed of a pCp core functionalized at its 7- and 15-positions respectively with 3-pyridyl and 4-pyridyl units. The self-assembly of pCpd4py with Pd 2+ metal ions afforded a [Pd3 (pCpd4py )6 ] 6+ cage structure, pCpd4py-Pd, where the six pCpd4py ligands doubly bridge each edge of the Pd3 triangular core. The ligand pCpd4py and the palladium cage pCpd4py-Pd have been characterized by NMR spectroscopy, ESI-MS spectrometry and X-ray diffraction analyses and their photophysical properties investigated by steady-state and time-resolved emission spectroscopy as well as time-dependent density functional theory calculations.